Site density models of inhomogeneous classical molecular liquids. (31st August 2018) - Valiev, Marat; Chuev, Gennady N
Abstract: We present a general framework for developing site density descriptions of inhomogeneous molecular liquids. It avoids explicit construction of full site density functional in lieu of self-consistent field equations, and easily accommodates the case of flexible molecules. We illustrate our methodology with two particular examples. The first one, cluster site density functional theory (CSDFT), is based on molecular gas reference with a specific cluster representation. The resulting approach provides natural separation between intra- and inter-molecular effects, leading to a compact analytical form for the self-consistent density equation similar to simple liquid theory. The second example is related to an existing three-dimensional reference interaction site model (3D-RISM). We demonstrate that 3D-RISM arises from a specific non-Hamiltonian based reference decomposition. We establish a connection between CSDFT and 3D-RISM, and use it to analyze intra-molecular and inter-molecular errors associated with the 3D-RISM description of an inhomogeneous dimer molecular liquid system. We observe that the main source of errors can be traced to insufficient description of inter-molecular effects in 3D-RISM theory, and intra-molecular errors are fairly small.